Banking and Finance facing new Policies related to Pandemics - Nejoum, Hasnaa Mohamed Alarabi (2022)
The dissertation highlights the challenges faced by the governments across the globe during the post-pandemic period. Moreover, the dissertation has presented how the governments implemented policies to keep the financial sector afloat in the time of global crisis. Literature from past global crises is incorporated to develop a better understanding of the need to implement policies to steer away the economy from collapsing. The dissertation focused on the factors that are responsible for implementing policies and what impact it had on the nations’ economy. Secondary research is conducted to gather relevant information about the Covid-19 global crisis and its impact on the financial sector. The aim of the research is to identify the policies which had negative or positive effects on the economy and compare it with the past global crisis, so that it can be determined how successful the governments were to mitigate the challenges in the current global crisis.